The Economy of Tourism and Its Impact to Other Sectors in Lampung Province - Faurani Santi Singagerda; Linda Septarina (Journal of Indonesian Tourism and Development Studies, 2016)
Tourism sector has been identified contribute to the economy of Lampung Province. The study aims to assess the direct and indirect linkage towards economic sectors, analyze the sensitivity of tourism sector distribution, to assess the multiplier effect of dispersion in the tourism sector, and calculate the final demand of tourism sector in the economy of Lampung Province. The results revealed that the score of the forward linkages from the tourism sector in Lampung is relatively small compared to the backward linkage. Both directly and indirectly, the tourism sector is a â€˜down streamâ€™ sector of Lampung economy, which the output is directly consumed by final consumers. Therefore if tourism sector is developed, it can pull output that is in the upstream sector.Keywords: development, forward and backward linkages, local economy, multiplier effect, tourism economy.Â